Analisis Pengaruh Kompensasi, Motivasi, Lingkungan Kerja, Kepemimpinan Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Intervening - Sumiatik Sumiatik; Sumitro Sarkum; Zuriani Ritonga (Akuntansi & Ekonomika, 2021)
This study aims to analyze the effect of compensation, motivation, work environment, leadership on employee performance with organizational commitment as an intervening variable. Data collection in this study was conducted through a survey approach with quantitative descriptive research type by distributing questionnaires to 217 respondents. The data analysis tool used in this study was SPSS (Statistical Product Software Solution). The results of this study indicate that partially compensation, motivation, work environment, leadership have a significant effect on Organizational Commitment. Compensation, motivation, work environment and leadership have a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance.